2015
DOI: 10.1089/biores.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Autophagy of Adipose-Derived Stem Cells Grown on Chitosan Substrates

Abstract: Autophagy is an important protein quality control mechanism for cells under stress conditions to promote cell survival. Modulation of autophagy on biomaterial substrates is rarely reported. In this study, the autophagy of adipose-derived stem cells (ADSCs) cultured on chitosan (CS) substrates was examined. Compared to the traditional monolayer culture, ADSCs cultured on CS substrates showed spheroid formation as well as a prolonged upregulation of autophagosomal marker-microtubule-associated protein 1 light ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It is generally accepted that molecules secreted from ADSCs may influence the effects of ADSCs on tumor growth. Therefore, the culture conditions of ADSCs may have an important role in determining the association between ADSCs and tumor cells, since various culture conditions could affect the secretion of molecules from ADSCs ( 32 , 33 ). Notably, Tian et al reported that human MSCs may inhibit proliferation of cancer cells in vitro and enhance tumor growth in vivo ( 34 ), thus suggesting that MSCs exert a dual effect on the same tumor under various growing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that molecules secreted from ADSCs may influence the effects of ADSCs on tumor growth. Therefore, the culture conditions of ADSCs may have an important role in determining the association between ADSCs and tumor cells, since various culture conditions could affect the secretion of molecules from ADSCs ( 32 , 33 ). Notably, Tian et al reported that human MSCs may inhibit proliferation of cancer cells in vitro and enhance tumor growth in vivo ( 34 ), thus suggesting that MSCs exert a dual effect on the same tumor under various growing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sphere or 3D culture methods may promote the secretion of cytokines and chemo kines from ADSCs ( 32 , 33 ); consequently, sphere or 3D culture conditions may theoretically enhance the effects of ADSCs on tumor cells. As predicted, the present study demonstrated that sphere or 3D culture methods could enhance the inhibitory effects of ADSCs on liver cancer cell migration, and could accelerate the effects of ADSCs on liver cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MSCs cultured on chitosan substrates show spheroid formation and upregulated expression of the autophagosomal marker LC3 II in a Ca 2+ -dependent manner, and these changes are accompanied by a higher survival rate in response to H 2 O 2 than in cells grown as a monolayer culture. In addition, chitosan substrates also increase the expression levels of the upper autophagy signal pathway-related proteins, including Ulk1, Atg-13, and autophagy/Beclin-1 regulator 1, both before and after the addition of H 2 O 2 compared with general culture conditions [58]. Jun et al argued that melatonin increases the levels of manganese superoxide dismutase (MnSOD) and catalase while suppressing H 2 O 2 -induced ER stress and autophagy to reduce the apoptosis rate of MSCs via upregulation of prion protein (PrP C ) [59].…”
Section: Autophagy Processmentioning
confidence: 99%
“…Autophagy, a process of cellular self-digestion, is considered to be a cytoprotective response that may occur after the withdrawal of growth factors or under stress conditions (for review see [ 24 ]). In this context, autophagy has also been identified as an essential mechanism for protecting MSCs and regulating bioenergetic requirements for stem cell activation [ 25 , 26 , 27 , 28 ]. On the other hand, initial data from experiments with ADMSCs have also shown that the downregulation of nuclear factor erythroid 2-related factor 2 (Nrf2)/HO-1 promotes autophagy-dependent osteoblastic differentiation, which indicates a negative regulation of autophagy by HO-1 in this cell type [ 29 ].…”
Section: Introductionmentioning
confidence: 99%